Analysis of Challenges to the Sustainability of Livestock Food System in Isiolo County, Kenya - Machan, Steve N.; Agwata, Jones F.; Oguge, Nicholas (My University, 2018)
Dryland landscapes experiences greater challenges in the regional and international trade for livestock and livestock products due to systems of production, quality control and safety measures. The objective of this study was to characterize livestock food system in Isiolo County and evaluate factors that affect the sustainability of the systems. The main value chains identified were camel milk, beef, sheep and goat products. The food system is driven by domestic trade which face greater threats to suffice sustenance in livestock and livestock products trade due to weak market integration and poor access to regional and international markets. Weak institutional coordination, insecurity and persistent droughts were notable barriers to sustainability of livestock food system in Isiolo County. Environmental degradation accruing from climate related risks and other stressors of biodiversity are also major threats to sustainable livestock production, hence affecting this livelihood system.
Keywords: Food system; Value chains; Food quality; Food safety; Regulatory framework